Optineurin suppression causes neuronal cell death via NF‐κB pathway. (17th June 2013) - Akizuki, Mayumi; Yamashita, Hirofumi; Uemura, Kengo; Maruyama, Hirofumi; Kawakami, Hideshi; Ito, Hidefumi; Takahashi, Ryosuke
Abstract Mutations in more than 10 genes are reported to cause familial amyotrophic lateral sclerosis (ALS). Among these genes, optineurin (OPTN) is virtually the only gene that is considered to cause classical ALS by a loss‐of‐function mutation. Wild‐type optineurin (OPTNWT) suppresses nuclear factor‐kappa B (NF‐κB) activity, but the ALS‐causing mutant OPTN is unable to suppress NF‐κB activity. Therefore, we knocked down OPTN in neuronal cells and examined the resulting NF‐κB activity and phenotype. First, we confirmed the loss of the endogenous OPTN expression after siRNA treatment and found that NF‐κB activity was increased in OPTN‐knockdown cells. Next, we found that OPTN knockdown caused neuronal cell death. Then, overexpression of OPTNWT or OPTNE50K with intact NF‐κB‐suppressive activity, but not overexpression of ALS‐related OPTN mutants, suppressed the neuronal death induced by OPTN knockdown. This neuronal cell death was inhibited by withaferin A, which selectively inhibits NF‐κB activation. Lastly, involvement of the mitochondrial proapoptotic pathway was suggested for neuronal death induced by OPTN knockdown. Taken together, these results indicate that inappropriate NF‐κB activation is the pathogenic mechanism underlying OPTN mutation‐related ALS. <boxed-text content-type="graphic" id="jnc12326-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Among the genes for typical amyotrophic lateral sclerosis (ALS) phenotypes, optineurin (OPTN) is virtually the only gene in which a loss‐of‐function mutation is considered as the principal disease mechanism. We found that OPTN knockdown induced neuronal cell death via NF‐κB activation. Furthermore, proapoptotic molecules such as p53 and Bax representing downstream targets of NF‐κB are suggested to be involved in neuronal death.